Kepentingan Nestlé Terhadap Kemenangan Indonesia Dalam Referendum Ekspor Kelapa Sawit Indonesia ke Swiss Tahun 2021 - Brilianto, Refinalditya Devatra (2022)
On March 7, 2021, a Referendum on Indonesian Palm Oil Exports to Switzerland was held. In the referendum, Indonesia won 51.6% of the Swiss population who agreed to continue the Comprehensive Economic Partnership Agreement (CEPA) between Indonesia and The European Free Trade Area (EFTA), a trading bloc consisting of Iceland, Norway, Liechtenstein, and Switzerland. Indonesia's narrow victory in the referendum could not be separated from the support of votes from the regions where agricultural commodity-based companies are based in Vaud and Geneva, which are the home of MNC Nestlé. This study uses 3 concepts to see what interests Nestlé has in Indonesian palm oil, namely by using the concept of Multinational Corporation, SDGs, and free trade. As a multinational company, Nestlé has its own interests in Indonesian palm oil because Nestlé helped Indonesia win in the Indonesian-Swiss palm oil referendum. These interests are Nestlé's Needs in Fulfilling Raw Materials, Reducing Production Costs (Cost Minimization) by Eliminating Raw Materials Import Fees, and Building a Positive Image of Indonesian Palm Oil, as well as Nestlé's Interests in the Market Needs in Indonesia.